RANCANG BANGUN APLIKASI PENGENDALIAN DOKUMEN KONTRAK KRU BERBASIS WEB PADA PT. RUKINA SUKSES ABADI - Hirwatinto, M. Arian; Sutanto, Teguh; Shintawati, Rahayu Arya (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
PT Rukina Sukses Abadi is a company working in the field of marine dredging and reclamation. Party crewing experience problems in the process of checking the contract of the crew. This happens because the contract checking of each crewÂ  done manually by looking at the documents one by one. It resulted in the checking process takes a long time. As a result, the company often late in making a contract extension. Crewing parties also have difficulty in knowing the status of the crew. Does the crew active or inactive, and the absence of a detailed report on the crew made it difficult for the manager to see the history of the crew. Based on these issues, it is proposed the creation of control applications of contract document of crew. This system is able to help the crewing in checking the contract of the crew and to find out the status and history of the crew. The trials results concluded that the control applications of contract document of crew is able to generate warning information of validity period of the contract of the crew which will expire, the status of the crew who is active or inactive, and profile reports for of managersâ€™ requirement